The THE STATE OF MENTAL HEALTH AND AVAILABLE SERVICES FOR POST-SECONDARY STUDENTS IN PAKISTAN; A GAP IN EDUCATIONAL INSTITUTION HEALTH POLICY - Tahir, Ayesha; Nasar, Almas; Sarwar, Huda; Saleem, Maria; Mazhar, Marium; younis, Rabia; Badiuzzaman, Sadaf; Rameez, Sahar (Journal of Pakistan Psychiatric Society, 2023)
We have explored the literature to evaluate the status of mental health among post-secondary students at the global and local levels with a special interest in medical students along with the detrimental effects on mental health caused by the CoVID-19 pandemic. The implementation strategies already developed and in the process by some countries to improve the mental health of post-secondary students are also covered in this review. The results of this literature review have brought to light the presence of a high number of mental health disorders among post-secondary students throughout the world including Pakistan which is further deteriorated by the negative effects of CoVID 19 pandemic. Several challenges and treatment gaps have been identified globally, especially in LMIC including Pakistan which shows a lack of data as well as a lack of services which warrants a need for a framework that will use a holistic approach to tackle these issues in post-secondary students.